Sistem Pakar untuk Menentukan Konsentrasi Mahasiswa Prodi Sistem Komputer Menggunakan Metode Forward Chaining - Boy Rizki Akbar; Muhammad Fahriza; , Fery Anugerah; Chelfina Utami; Laila Maghfirah; Rian Farta Wijaya; Zulham Sitorus (CV. Hawari, 2025)
Determining a concentration is one of the obligations for computer systems students because it has a direct impact on their careers and individual potential development. However, most students determine their concentration based on general perceptions without understanding their personal interests and talents, job trends, or even following their friends' choices. Therefore, this study aims to help students recognize their potential, interests, and abilities in choosing the right concentration. This study uses the Forward Chaining method, which is an expert system-based approach oriented towards factual data to draw conclusions and provide relevant recommendations. In its implementation, the system will process inputs in the form of interests, talents, and ability assessment results, then trace logical rules to determine the most suitable concentration. The final result of the research is expected to produce visual recommendations in the form of percentages, which show the level of compatibility between students' interests and talents with various concentration options. The system is expected to support a more objective, systematic, and data-driven academic decision-making process so that students can optimize their potential to the maximum.